PENCEGAHAN OVERHEATING MELALUI EDUKASI PERAWATAN PADA KENDARAAN RODA DUA - Fajarudin, Adam; Hasibuan, Akmal Rizki Gunawan; Marginingsih, Ria (Universitas Islam 45 Bekasi, 2024)
Overheat is a condition when a vehicle's engine temperature reaches a higher level than it should and cannot be maintained at a normal operating temperature. This is a serious problem that can cause damage to the engine if not addressed immediately. The purpose of this community service program is to prevent overheating in Sukaragam Village by educating the community about two-wheeled vehicle maintenance. Therefore, this community service aims to complete community service by providing counseling on simple maintenance of motorized vehicles. The community service method applies counseling in the form of brief socialization and training on how to care for motorbikes to avoid overheating. The success of this community service activity is expected to reduce cases of overheating in two-wheeled vehicles in the community. With a better understanding of vehicle maintenance, it is hoped that the community can take preventive actions such as checking the condition of the engine coolant regularly, using the appropriate oil, and avoiding driving when the engine is too hot. This not only improves driving safety, but also extends the life of the vehicle and reduces repair costs. In addition, this activity also contributes to reducing exhaust emissions produced by motor vehicles, thus supporting environmental conservation efforts.